UNHCR calls for concerted action as forced displacement hits new high of 110 million | UN News - United Nations Human Rights Council (UNHRC) (UN News, 2023)
The full-scale war in Ukraine, alongside other conflict and climate-driven upheaval, meant more people than ever remained uprooted from their homes last year, heightening the urgency for immediate, collective action to alleviate the global crisis, the UN refugee agency (UNHCR) said on Wednesday.
Worldwide
Keywords: 2023-06 June